A Low Cost Of Simple Pendulum Experiment Apparatus Based On Ultrasonic Sensor And Arduino Microcontroller - W. S. Mada Sanjaya; Dyah Anggraeni; Rena Denya; Handi Pandriantama; Iklimah Iklimah; Indry Pritanti Dewi (Pusat Pengabdian kepada Masyarakat LP2M UIN Sunan Gunung Djati Bandung, 2018)
Simple Pendulum is a basic physics experiment about observation of harmonic oscillation motion. Generally, this experiment is performed with manual measurements and observations that are less efficient. In this paper describe numerical simulations of Simple Pendulum motion based on Python 2.7. The experimental system of real-time Simple Pendulum based on HC-SR04 Ultrasonic Sensor, Arduino microcontroller and the interface using Python 2.7. The experimental results show good agreement when compared with the numerical simulations. The advantage of this system is open source that makes physics experiments easier and low cost.